Gluconeogenesis and Glycogen Metabolism (Henry Stewart Talks, 2026)
Gluconeogenesis regulation, Glycogen metabolism processes, Key enzymes in glucose pathways, Hormonal control of metabolism, Biochemical adaptation fasting/exercise, Metabolic disease implications, Substrate cycles energy efficiency